Total phenolic content, quercetin, and antioxidant activity of gandaria (Bouea Macrophylla Griff.) leaf extract at two stages of maturity - Hardinsyah, Hardinsyah; Windardi, Ika Puspa; Aries, Muhammad; Damayanthi, Evy (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
The aim of this study was to determine the effect of leaf maturity stage and extraction solvents on Total Phenolic Content (TPC), quercetin, and antioxidant activity of gandaria leaves as well as the relationship of TPC and quercetin content to antioxidant activity. In this study, leaves were extracted using maceration method with three different solvents (96% ethanol, ethyl acetate, and hexane) followed by evaporation using rotary evaporator to obtain Crude Extracts (CE). Tender and mature gandaria leaves from Indonesian Institute of Science were examined for TPC and quercetin content. Measurement of antioxidant activity were performed by Ferric Reducing Antioxidant Power (FRAP) method. The antioxidant compound analysis indicated that hexane extract of mature gandaria leaves contained the highest TPC and quercetin content (30.84±0.54 mg GAE/g and 4.36±0.23 mg QE/g, respectively). Meanwhile, the ethanol extract of mature gandaria leaves demonstrated the highest reducing power (5.62±0.38 mg FeSO4 equivalent/g). These findings showed positive correlation between TPC and reducing power as well as quercetin and reducing power from gandaria leaf extracts depending on their maturity stage and extraction solvents. In addition, mature gandaria leaves had better extraction yield, making it potential for development of functional food.